2020
DOI: 10.1021/acs.joc.0c01191
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sea Cucumber Saponins with Antitumor Activities

Abstract: Holostane glycosides are characteristic metabolites of sea cucumbers, which possess various biological activities. Here, we report the synthesis of two representative congeners, namely, pervicoside B and C, starting from lanosterol with the longest linear sequence of both 34 steps and in 0.3% overall yields. The flexible synthetic approach has enabled us to expeditiously prepare 16 analogues for preliminary studies on the key structural features influencing their antiproliferative activities against tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Syntheses of steroid tetrasaccharides pervicoside B and C ( Holothuria pervicax ) have been reported as part of a SAR study of holostane glycosides; variation in cytotoxicity was observed with changes to the aglycone structure and the number of saccharide residues. 726 Spinochrome/echinochrome pigments originally isolated from sea urchins are still subjects of interest, with a simple conversion of urchin pigment spinochrome E into the sea cucumber pigment namakochrome reported. 727 Echinamines A and B were found to exhibit virucidal activity towards herpes simplex virus (HSV)-1 when the virus was pretreated with the test compounds, 728 and the products of oxidative degradation of echinochrome A have been characterised.…”
Section: Echinodermsmentioning
confidence: 99%
“…Syntheses of steroid tetrasaccharides pervicoside B and C ( Holothuria pervicax ) have been reported as part of a SAR study of holostane glycosides; variation in cytotoxicity was observed with changes to the aglycone structure and the number of saccharide residues. 726 Spinochrome/echinochrome pigments originally isolated from sea urchins are still subjects of interest, with a simple conversion of urchin pigment spinochrome E into the sea cucumber pigment namakochrome reported. 727 Echinamines A and B were found to exhibit virucidal activity towards herpes simplex virus (HSV)-1 when the virus was pretreated with the test compounds, 728 and the products of oxidative degradation of echinochrome A have been characterised.…”
Section: Echinodermsmentioning
confidence: 99%
“…Interesting studies concerning the total 1 chemical synthesis of sea cucumber glycosides are also known. 14,15 Recently, significant progress in chromatographic methods of separation and physicochemical methods of structural analysis of natural products has been achieved, mainly through 2D-NMR spectroscopic procedures and high resolution mass-spectrometry. As result, many dozens of new structures of sea cucumber triterpene glycosides have been discovered, which remain outside of earlier reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting studies concerning the total chemical synthesis of sea cucumber glycosides are also known. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…The combined organic layers were washed with brine, dried over Na2SO4 and then filtered. The filtrate was concentrated in vacuo, which was used directly in the next step (an aliquot of crude product was purified with silica column chromatography for analytical purposes (11). LiAlH4 (16.25 g, 1.1 eq) was suspended in THF (1 L) and cooled to 0 °C.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Meanwhile, because glycosidic bonds are not stable under many reaction conditions, such as acidic conditions, conventional strategies for glycoside synthesis involve glycosylation at the late stage in the reaction. [9][10][11] To accomplish this, we would have to rely on putting orthogonal protecting groups to differentiate the 3′-and 4′-hydroxyl groups so that the glycosylation at the desired site could be ensured. Our previous efforts to synthesize piceatannol-3′-O--D-glucopyranoside, which have been reported under a Chinese patent, followed this strategy (see Scheme 1).…”
mentioning
confidence: 99%